1996
DOI: 10.1152/ajpgi.1996.271.4.g555
|View full text |Cite
|
Sign up to set email alerts
|

A low-protein diet ameliorates disrupted diurnal locomotor activity in rats after portacaval anastomosis

Abstract: In previous studies we noted a disruption of the circadian locomotor activity rhythm in rats after portacaval anastomosis (PCA). To examine whether this abnormality is related to factors that aggravate hepatic encephalopathy in humans, we studied the effect of dietary formulation and protein content on body weight, locomotor activity, and entrainment to the light-dark cycle in rats after PCA or sham operation. Postoperative weight loss was prevented by pair-feeding with a purified liquid diet. However, the beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…Specifically, the mean escape latencies to the platform increased significantly in the TAA animals that received the high protein diet compared to those who only received the TAA hepatotoxin (mean increase of 11.93 s), and compared to the control groups (mean increase of 22.95 s). The hyperproteic diet might exacerbate the learning impairments presented in this model through the mediation of gut-derived toxins entering the brain [34,48]. Spatial learning impairment was also aggravated after feeding bile duct-ligated rats a high ammonia diet [49].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Specifically, the mean escape latencies to the platform increased significantly in the TAA animals that received the high protein diet compared to those who only received the TAA hepatotoxin (mean increase of 11.93 s), and compared to the control groups (mean increase of 22.95 s). The hyperproteic diet might exacerbate the learning impairments presented in this model through the mediation of gut-derived toxins entering the brain [34,48]. Spatial learning impairment was also aggravated after feeding bile duct-ligated rats a high ammonia diet [49].…”
Section: Discussionmentioning
confidence: 87%
“…However, although recent research no longer supports this idea, clinicians still report that diets rich in meat protein should be avoided by HE patients [33]. Moreover, variations in the protein concentration have been shown to have an influence on the behavioral symptoms presented in an experimental rat model of HE due to hepatic devascularization [34]. As far as we know, no published experimental studies have shown the effects of a high protein diet on cognitive function in an animal model of HE and on the neuronal metabolic activity of regions known to be involved in the cognitive process.…”
mentioning
confidence: 99%
“…When placed under con ditions of constant illumination, allowing the expression of the circadian rhythm, many ani mals lose the ability to have a 'free-running' rhythm. As the abnormalities in entrainment improve with measures used in the treatment of hepatic encephalopathy [38], it is possible that the SCN and/or its afferent/efferent con nections arc affected by the encéphalopathie process. In this regard, preliminary studies indicate that ammonia may exert direct ef fects on the pineal gland [39], Ammonia also increases the entry of tryptophan, the seroto nin precursor, into brain; it is possible that changes in melatonin may reflect altered serotoninergic pathways seen in hepatic encepha lopathy [40], In the second, high endogenous levels of melatonin seen during daytime as a result of decreased hepatic elimination may be the main cause for a phase shift in the melatonin rhythm itself.…”
Section: Clinical Studymentioning
confidence: 99%
“…Recent technological advances, such as brain microdialysis, for example, have allowed measurements of transmitters in the extracellular space [199,200]. Improved methods for monitoring behaviour in small rodents are also becoming available [201]. A recent study on portocaval-shunted rats, which employed electrophysiological and behavioural approaches in the individual animal, showed deficits in corticostriatal synaptic plasticity, which could be related to a disturbed processing of novel information and memory [202].…”
Section: Alterations In Neurotransmissionmentioning
confidence: 99%